Validation of Point-of-Care Ultrasound to Measure Perioperative Edema in Infants With Congenital Heart Disease - Persson, Jessica N.; Holstein, Jacqueline; Silveira, Lori; Irons, Aimee; Rajab, Taufiek Konrad; Jaggers, James; Twite, Mark D.; Scahill, Carly; Kohn, Mary; Gold, Christine; Davidson, Jesse A. (Frontiers in Pediatrics, 2021)
Purpose: Fluid overload is a common post-operative issue in children following cardiac surgery and is associated with increased morbidity and mortality. There is currently no gold standard for evaluating fluid status. We sought to validate the use of point-of-care ultrasound to measure skin edema in infants and assess the intra- and inter-user variability. Methods: A prospective cohort study of neonates (≤ 30 d/o) and infants (≤ 12 m/o) undergoing cardiac surgery as well as neonatal controls. Skin ultrasound was performed on four body sites at baseline and daily post-operatively through post-operative day (POD) 3. Subcutaneous tissue depth was manually measured. Intra- and inter-user variability was assessed using intraclass correlation coefficient (ICC). Results: 50 control and 22 surgical subjects underwent skin ultrasound. There was no difference between baseline surgical and control neonates. Subcutaneous tissue increased in neonates starting POD 1 with minimal improvement by POD 3. In infants, this pattern was less pronounced with near resolution by POD 3. Intra-user variability was excellent (ICC 0.95). Inter-user variability was very good (ICC 0.82). Conclusion: Point-of-care skin ultrasound is a reproducible and reliable method to measure subcutaneous tissue in infants with and without congenital heart disease. Acute increases in subcutaneous tissue suggests development of skin edema. There is evidence of skin edema starting POD 1 in all subjects with no substantial improvement by POD 3 in neonates. Point-of-care ultrasound could be an objective way to measure extravascular fluid overload in infants. Further research is needed to determine how extravascular fluid overload correlates to clinical outcomes.